2021
DOI: 10.1530/eje-20-1387
|View full text |Cite
|
Sign up to set email alerts
|

Kallmann syndrome in a patient with Weiss–Kruszka syndrome and a de novo deletion in 9q31.2

Abstract: Patients with deletions in chromosome 9q31.2 may exhibit delayed puberty, craniofacial phenotype including cleft lip/palate, and olfactory bulb hypoplasia. We report a patient with congenital HH with anosmia (Kallmann syndrome, KS) and a de novo 2.38 Mb heterozygous deletion in 9q31.2. The deletion breakpoints (determined with whole genome linked-read sequencing) were in the FKTN gene (9:108,331,353) and in a non-coding area (9:110,707,332) (hg19). The deletion encompassed six protein-coding genes (FKTN, ZNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…6 B) ( Niehrs and Meinhardt, 2002 ; Scholpp et al, 2004 ) . When we examined the expression of 32 genes linked to CHH+anosmia ( Cho et al, 2019 ; Messina et al, 2020 ; Iivonen et al, 2021 ) after 2 days of FGF8, we found that ten of these genes to be differentially expressed ( ).…”
Section: Resultsmentioning
confidence: 99%
“…6 B) ( Niehrs and Meinhardt, 2002 ; Scholpp et al, 2004 ) . When we examined the expression of 32 genes linked to CHH+anosmia ( Cho et al, 2019 ; Messina et al, 2020 ; Iivonen et al, 2021 ) after 2 days of FGF8, we found that ten of these genes to be differentially expressed ( ).…”
Section: Resultsmentioning
confidence: 99%
“…We present three patients with intellectual disability/global developmental delay and craniofacial dysmorphisms with interstitial deletions of the 9q31 chromosome region. Deletions in this region are relatively uncommon and there have been less than three dozen cases reported in the literature (Cao et al, 2015; Chien et al, 2010; Dugan et al, 2018; Gamerdinger et al, 2008; Iivonen et al, 2021; Mucciolo et al, 2014; Ramineni et al, 2019; Xu et al, 2013) and DECIPHER database (Firth et al, 2009) (DECIPHER ID: 270439, 250,887, 261,011, 253,228, 256,779, 286,220, 280,899, 252,795, 267,903, 296,377, 248,259, 274,871, 359,751, 394,934, 402,156, 402,516) (Figure 2). Common craniofacial dysmorphisms in this cohort include bilateral ptosis, arched eyebrows, a broad nasal root, low forehead, low set ears, anteverted nares, palate abnormalities, and a long philtrum.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging information about one of these interstitial microdeletions (9q31) suggests that the haploinsufficiency of this region may cause a recognizable microdeletion syndrome. To date there have been several cases reported in the literature (Cao et al, 2015; Chien et al, 2010; Dugan et al, 2018; Gamerdinger et al, 2008; Iivonen et al, 2021; Mucciolo et al, 2014; Ramineni et al, 2019) and over a dozen additional cases recorded in DECIPHER (Firth et al, 2009). These cases share many phenotypic similarities such as developmental delay/intellectual disability, hearing loss, short stature/growth retardation, microcephaly (<10th percentile) and distinctive facial features of ptosis, arched eyebrows, and ear malformations.…”
Section: Introductionmentioning
confidence: 99%
“…The second strongest signal is observed for chromosome 9q31.2 (rs630965, p meta = 1.01 × 10 −63 ). Patients with deletions on 9q31.2 may have delayed puberty (Iivonen et al, 2021). The third strongest signal observed on BNC2 (rs3814113, p meta = 2.16 × 10 −43 ) is a putative tumor suppressor gene in highgrade serous ovarian carcinoma, which impacted cell survival after oxidative stress (Cesaratto et al, 2016).…”
Section: Breast and Ovarian Cancermentioning
confidence: 99%